Heterosis and combining ability for leaf yield and its components in vegetable amaranth (Amaranth us tricolor) - REDDY, V V PRATAP; VARALAKSHMI, B (The Indian Journal of Agricultural Sciences, 2013)
Heterosis, general and specific combining ability variances and their effects were studied for nine characters in linex tester design in vegetable amaranth (Amaranthus tricolor L.). The results indicated the pre-dominance of non-additivegene action for plant height, leaf number, leaflength, leaf breadth, stem girth, stem weight, leaf weight and plant weight.Additive gene action was preponderant for leaf stem ratio. Significant heterosis over both the better and mid-parents wasexpressed by 'AV 22' X 'AV 69' for plant height, 'AV 6' x 'AV 69' for plant weight. The best combiners were 'AV 6','AV 22' among the 5 lines and 'AV 69' of the 2 testers. Based on both the specific combining ability effects and meanperformance, cross' AV 31' x 'AV 69' was found to be superior for plant yield and its attributes, viz leaf breadth, stemgirth, stem weight and leaf weight.